Answer:
see explanation
Explanation:
Using the rules of exponents
×
⇔
![a^((m+n))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pbs04glo0orkv044hrexowjp79j4x1zk97.png)
⇔
![a^((m-n))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sgj3651he0sqhsnz8zm9z9hgyy0ympoj8b.png)
(5)
Split the factors into like terms
=
×
×
![(y^(8) )/(y^(3) )](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fk5cn09i775opetk1kmpy3xy9bh6otjhp4.png)
= 5 ×
×
![y^((8-3))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vc82juvgy2j1nqfkbunnuyu1q51s9kmm0g.png)
= 5x³
![y^(5)](https://img.qammunity.org/2020/formulas/mathematics/high-school/b1763mlx8iirszajt0m6m6sls3vzlf04j5.png)
(6)
Consider the left side
=
=
, then
=
![y^(-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jb8ce367gj1ahllg8xnkk4zkckipvm22hb.png)
Since the base on both sides is y, equate the exponents
2 + n = - 3 ( subtract 2 from both sides )
n = - 5